Mourning and Management of the COVID-19 Health Emergency in the Priestly Community: Qualitative Research in a Region of Northern Italy Severely Affected by the Pandemic - Testoni, Ines; Zanellato, Silvia; Iacona, Erika; Marogna, Cristina; Cottone, Paolo; Bingaman, Kirk (Frontiers in Public Health, 2021)
Background: The COVID-19 pandemic is causing major social changes to which significant psychological effects are linked. During the first phase of the pandemic wave in Italy, whilst there was insufficient information about the phenomenon and the strategies to safeguard the population against it, many categories of people, whose professions required constant contact with the public, were affected by the contagion. Aims: The literature has shown how religiousness can support the management of stress due to diseases and health risks. In relation to this, the current study wanted to investigate how priests managed the early stages of the pandemic. This work, therefore, aimed to investigate the psychological experiences related to the contagion and the eventual death of colleagues as well as the resilience strategies activated by the priests during the process. Participants: The research involved 12 Catholic priests, all male and aged between 42 and 63 years. They came from the same pastoral community in one of the regions in Northern Italy that were most affected during the first phase of the pandemic. Those ministers had been constantly in contact with the faithful of their parishes since the breakout of the virus. Methodology: A qualitative research design was adopted, and in-depth interviews were conducted. The dialogues aimed at investigating the deep, personal and relational experiences of the priests, together with their concerns and the tools they adopted to manage anxiety. The texts obtained from the interviews were subjected to thematic analysis. Results: The areas studied concerned the experiences of the participants during the lockdown, the implications of social distancing and lack of funeral rituality and, finally, the importance of prayer as a resilience factor. Conclusions: In the current scenario dominated by the pandemic, it is significant and stimulating to understand and reflect on the functions and roles of the experiences of faith, particularly the act of elaborating the process of mourning due to COVID-19.